Evaluation of Fungal Flora in Some Important Nut Products (Pistachio, Peanut, Hazelnut and Almond) in Tehran, Iran - Khosravi, Ali Reza; Shokri, Hojjatollah; Ziglari, Tahereh (Pakistan Journal of Nutrition, 2007)
The natural occurrence of fungal contamination was evaluated in stored nuts including pistachio, peanut, hazelnut and almond selected randomly from different regions of Tehran. After initial preparation, the samples were cultured on Sabouraud glucose agar, Dichloran rose-bengal agar and Czapek-dox agar. A total of 60 samples were analyzed and 158 fungal isolates were identified. Mycological analyses revealed that the most frequent isolated fungi from different nuts were Aspergillus (32.2%), Penicillium (30.3%), Mucor (17.1%), Fusarium (18.2%), Paecilomyces (6.9%) and yeast (5.1%). Significant difference was observed between the frequency of fungal isolates of pistachio, peanut and hazelnut with almond (p<0.05). The results demonstrated that nut samples with a relative high incidence of diverse species of fungi to need for proper surveillance and monitoring exclusively for the prevention of fungal and mycotoxin contaminations before it reaches the consumer.